The simplification of the expression [tex]xy-5x+y^2xy-5x+y ^2[/tex] gives - 335.
Usually, simplification involves proceeding with the pending operations in the expression.
Simplification usually involves making the expression simple and easy to use later.
Given;
[tex]xy-5x+y^2xy-5x+y ^2[/tex]
Substitute x = -3 and y = 5.
[tex]-3\times 5-5\times -3+5^2\times -3\times 5-5\times -3+5 ^2[/tex]
= -15 + 15 - 375 + 15 + 25
= -335
Learn more about simplification;
https://brainly.com/question/17579585
#SPJ1